Development of new systematic techniques for retrofit of water network - 393847 Zainuddin Abdul Manan; Universiti Teknologi Malaysia. Fakulti Kejuruteraan Kimia dan Kejuruteraan Sumber Asli (Skudai, Johor : Penerbit UTM, 2008)
Includes bibliographical references